Stimulation Of Children Growth As A Result Of Tsunami Impact South Sunda Pandeglang Banten - Sugeng Wiyono; Iskari Ngadiarti; Isti Rusdiyani (SANITAS: Jurnal Teknologi dan Seni Kesehatan, 2019)
The cause of malnutrition is not only caused by lack of food intake but also because of infection. Another factor that is estimated to influence nutritional status is parenting. This study aims to find out the effect of mother class programs and child preschool toward mother's knowledge, parenting, children's nutritional intake, and children nutritional status. The hypothesis of this study is the intervention of the mother class program and pre-school plays better than the intervention of the mother class only or toward the mother's knowledge and nutritional status of the child. The chosen sample was children aged 2-6 years the inclusion and exclusion criterias. This study uses a quasi-experimental design. The sample was divided into 3 groups, mother group class, pre-school and mother and child play class. The results showed 73.3% of female research subjects, an average age of 55.84 months, 13.3% diarrhea, 2.2% ARI, 66.7%, coughs, 86.7% colds/flu, and 55.6% of children were permissively care. At the end of the treatment an in body weight increase, height of the child, the greatest nutritional status occurred in pre- school. At the end of the treatment the intake of nutrients in energy, protein, the fast is greatest fast is pre school group for the greatest intake of carbohydrates in the maternal class group. Health and nutrition education needs to be carried out on an ongoing basis to maintain the spirit of the mother to carry out health care for children and other families. It is necessary to find a form of playing patterns that can make a child enthusiasm for learning.